1976
DOI: 10.1159/000180578
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Extracapillary Proliferation

Abstract: Renal biopsy and clinical data from 60 patients with extracapillary proliferation (crescent formation) in > 50% of glomeruli were correlated. Nephropathy was related to infection (15 cases) malignancy (4 cases) and trichlorethylene exposure (2 cases). Isolated proteinuria was found 0.5–20 years before biopsy in 16 patients. Outcome was significantly related to percentage of crescentic involvement. Oligoanuria and impaired function at presentation were bad prognostic signs but preceding infection was favourable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…Nevertheless, our find ings. like the observations of Whitworth et al [14] and Petzel et al [15] support the idea that crescentic GN can occur as a paraneoplastic syndrome distinct from those renal lesions previously reported to be associated with malignancy.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, our find ings. like the observations of Whitworth et al [14] and Petzel et al [15] support the idea that crescentic GN can occur as a paraneoplastic syndrome distinct from those renal lesions previously reported to be associated with malignancy.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, crescentic GN is not usually thought of as a complication of malignancy despite the fact that in a large clinicopathologic study of crescentic GN, 4/60 (7%) of patients had malignancy [14], Our series suggests that 'idiopathic' crescentic GN may indeed be a renal lesion associated with malignancy. 7 of 80 patients with cres centic GN had an associated malignancy.…”
Section: Discussioncontrasting
confidence: 54%
“…In our opinion extracapillary lesions, which have frequently been described, also deserve consideration: the relationship between crescentic glomerulonephritis and malignancies and the significance of this relation ship have been recently underlined [28][29][30].…”
Section: Discussionmentioning
confidence: 91%
“…The retrospective series of Whitworth et al [2] found 4/60 patients with carcinoma who subsequently manifested crescentic glo merulonephritis, and Biava et al [3] noted 7/81 in their series. Notably, 9 of these cases occurred after the tumour was found, at inter vals up to 3 years.…”
Section: Sim Ultaneous Presentation Of G Astric Carcinom a And Crescementioning
confidence: 94%